Can advertising enhance consumers' desirable COVID‐19 health behavioral intentions? The role of brand‐pandemic fit. Issue 4 (3rd February 2022) - Özsomer, Ayşegül; Güzel, Zeynep Müge; Newmeyer, Casey E.; Schmidt‐Devlin, Ellen
Abstract: This article explores the fit between the advertised brand and the pandemic as a potential influence on consumers' intentions to engage in socially responsible health behaviors (social distancing, mask wearing, and getting tested when exposed). In an advanced and emerging market setting we find that advertisements for brands that are perceived as high on brand‐pandemic fit enhance consumers' socially desirable COVID‐19 health behavioral intentions and changes in brand credibility is the mechanism that drives such intentions. Fit is especially beneficial on the intentions of consumers whose health beliefs reflect only low to moderate concern about COVID‐19. Consumers with low or moderate (vs. high) COVID‐19 health beliefs exhibit an increased susceptibility to the fit—desirable health behavioral intentions relationship. The results are also corroborated in an emerging market context. Together, the results establish links between brand‐pandemic fit of advertisements, brand credibility, health beliefs, and consumers' intentions to engage in socially desirable health behaviors. The results suggest that advertising can play a role in encouraging desirable health behaviors and can promote consumer welfare via ads of high fit products and services that provide benefits during the pandemic in both advanced and emerging markets.